Multiple restriction fragment length polymorphisms at the insulin receptor locus: a highly informative marker for linkage analysis. - Elbein, S C (1986)
Although resistance to insulin action is a well-studied phenomenon in non-insulin-dependent diabetes and certain genetic syndromes, the role of inherited defects of the insulin receptor in these disorders is unknown. To facilitate the evaluation of that role, restriction fragment length polymorphisms (RFLPs) were identified using various portions of the insulin receptor cDNA to examine digested DNA from American Blacks, Pima Indians, and Caucasians. Five RFLPs were identified in Caucasians. Two of these were detected with a single 1.3-kilobase probe in Rsa I digests with minor allele frequencies of 0.48 and 0.23. An additional RFLP was noted with Bgl II and two more RFLPs with Sac I using a different 1.6-kilobase probe, with minor allele frequencies of 0.17 for Bgl II and 0.12 for both Sac I RFLPs. All RFLPs except for the second Sac I RFLP were present in American Blacks, while only the Rsa I RFLPs were present in Pima Indians. Pairwise analysis showed random association between all sites except for the Bgl II and second Rsa I sites, where the disequilibrium statistic, delta, was -0.70 (different from 0 at P less than 0.001). No association of any RFLP was noted with non-insulin-dependent diabetes in a small population. These studies show that this is a highly informative locus that should be important for mapping of chromosome 19p and for linkage studies.